2011
DOI: 10.1038/nm.2540
|View full text |Cite
|
Sign up to set email alerts
|

Key contribution of CPEB4-mediated translational control to cancer progression

Abstract: Malignant transformation, invasion and angiogenesis rely on the coordinated reprogramming of gene expression in the cells from which the tumor originated. Although deregulated gene expression has been extensively studied at genomic and epigenetic scales, the contribution of the regulation of mRNA-specific translation to this reprogramming is not well understood. Here we show that cytoplasmic polyadenylation element binding protein 4 (CPEB4), an RNA binding protein that mediates meiotic mRNA cytoplasmic polyade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
186
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(190 citation statements)
references
References 56 publications
4
186
0
Order By: Relevance
“…In agreement with a role for CPEB in tumor growth, the CPEB1 paralog CPEB4 regulates the translation of a group of proteins necessary for pancreatic ductal adenocarcinoma growth, invasion, and vascularization (28). Originally thought to differ in their mRNA targets (29), recent studies have shown that CPEB4 does recognize and bind to some of the same CPE targets as CPEB1, though with a lower affinity (30,31).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In agreement with a role for CPEB in tumor growth, the CPEB1 paralog CPEB4 regulates the translation of a group of proteins necessary for pancreatic ductal adenocarcinoma growth, invasion, and vascularization (28). Originally thought to differ in their mRNA targets (29), recent studies have shown that CPEB4 does recognize and bind to some of the same CPE targets as CPEB1, though with a lower affinity (30,31).…”
Section: Discussionmentioning
confidence: 88%
“…Originally thought to differ in their mRNA targets (29), recent studies have shown that CPEB4 does recognize and bind to some of the same CPE targets as CPEB1, though with a lower affinity (30,31). For example, like CPEB1 in hippocampal neurons, CPEB4 has been shown to bind and regulate tPA in both normal and cancerous pancreatic tissue (28). Interestingly, several reports implicate a downregulation of CPEB1 in cancer (32)(33)(34), whereas the results presented here suggest that an increase in CPEB1-mediated translation may support the progression of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This variant is located approximately 400 kb from HMGCR3, involved in lipid metabolism and shown to be associated with total cholesterol [32]. The biological mechanisms by which the remaining obesity-susceptibility loci might affect glucose (RBJ, CPEB4) and lipid metabolism (MTCH2) are less well understood [40][41][42] and require further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer development is closely related to the reprogramming of gene expression and genetic derangement contributes to cell proliferation, apoptosis, metabolism, invasion and malignant transformation (18,19). CPEBs control cellular proliferation, chromosome segregation and cell differentiation; aberrant expression of CPEBs correlates with certain types of cancer, indicating that cytoplasmic RNA 3' end processing is important in the control of tumor cell growth (1,19,20).…”
Section: Cpebs and Cancermentioning
confidence: 99%
“…CPEBs control cellular proliferation, chromosome segregation and cell differentiation; aberrant expression of CPEBs correlates with certain types of cancer, indicating that cytoplasmic RNA 3' end processing is important in the control of tumor cell growth (1,19,20). Several CPEBregulated mRNAs regulate cell-cycle progression, senescence and cell polarity (20).…”
Section: Cpebs and Cancermentioning
confidence: 99%